PEMBELAJARAN KOOPERATIF TIPE MASTERY LEARNING DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) SISWA KELAS VII MTS AL- MUNAWWROH BANGKO - Sintia Wulandari; Rozana Zuhri; Pitri Handayani (Pendidikan Biologi STKIP YPM Bangko, 2021)
Based on observations at MTs Al-Munawwaro Bangko, especially class VII, there are problems faced by students in the learning process, especially integrated science subjects. Some of the problems faced by students are that most of the integrated science learning outcomes of grade VII students have not reached the KKM set by the school, the model applied by the teacher has not varied, students' lack of interest in learning and students are embarrassed to ask about material that they do not understand, this results in low student learning outcomes. The purpose of this study was to decide the differences in students' integrated science learning outcomes using the cooperative model of the mastery learning type and the cooperative model of the team games tournament (TGT) type. This research is a comparative research. In this study, the sampling technique used a simple random sampling technique while the research instrument used a test in the form of essay questions. To test the hypothesis in this study using a t-test with α = 0.05. Based on the results of the study, it shows that the learning outcomes of students who are taught using the cooperative mastery learning model get a higher average learning outcome of 80.68 than the learning outcomes of students who are taught using the team games tournament (TGT) type cooperative model to get the average learning outcomes. Of 76.22. So that after being analyzed using the t-test, Ha was accepted and Ho was rejected, which means that there is a significant difference between the results of integrated science learning using a cooperative model of mastery learning type and a cooperative model of team games tournament (TGT) type for MTs Al-Munawwaroh Bangko class students.